DAI betwixt and between: from 'intelligent agents' to open systems science - Hewitt, C.; Inman, J. (IEEE transactions on systems, man, and cybernetics, 1991)
The authors discuss the development of open systems science (OSS) beginning with its roots in the fundamentals of concurrency. The nature of actors., which are the primitives of concurrency, is considered. The aim of OSS is to provide a foundation for effective technological solutions to the complex problems of large-scale open systems by providing a scientific discipline that focuses on issues of robustness, manageability, and scalability. In the large-scale open systems of the future, the focus with shift from centralized systems toward decentralized ones, with an emphasis on conflict processing. The evolution of this paradigm presents some challenges and some fruitful new ideas for distributed artificial intelligence that are discussed.< >